Upaya Meningkatkan Hasil Belajar Peserta Didik XI-2 Materi Matriks Melalui Pembelajaran Kooperatif Tipe STAD Di SMA Negeri 6 Surabaya Tahun Ajaran 2023/2024 - Dovina Meilisa Nur Fadilla; Herfa Maulina Dewi Soewardini; Sri Utami (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The cause of the low learning outcomes of students on matrix material is the lack of understanding of concepts and communication skills. A learning model that overcomes these problems is needed. The STAD type cooperative learning model can increase the interaction between students so that students can communicate and collaborate to understand matrix concepts. This class action research aims to improve students' learning outcomes on matrix material by applying the STAD type cooperative learning model in class XI-2 SMA Negeri 6 Surabaya. The data collection techniques used were observation, learning outcomes test, and documentation. The results showed that by applying the STAD type cooperative learning model can improve the learning outcomes of students of class XI-2 SMAN 6 Surabaya on matrix material. This is indicated by an increase in the value of learning outcomes and completeness of students after being given action in each cycle. There was an increase in learning outcomes by 39.39% from pre-cycle to cycle I and 54.54% from cycle I to cycle II. Learning completeness reached 54.54% in cycle I and 100% in cycle II.